Cinemática da cintura escapular, coluna cervical e torácica em idosos com doença pulmonar obstrutiva crônica - Claudia Silva Dias (2007)
Individuals with COPD exhibit lung hyperinflation, changing the conformity of the thorax and possibly altering the biomechanics of the scapula and spine. The present study investigated the kinematics of the scapula, cervical and thoracic spine in individuals with COPD, comparing them to an age-paired group without the disease. Methods: Nineteen individuals with COPD, at an average age of 74.2 years (SD 5.1), and 19 without the disease, at an average age of 71.9 years (SD 4.6), participated in the study. The Qualisys motion system was used for the 3D reconstruction of the specific anatomical points. Upward rotation, anterior tilt and internal rotation angles were obtained, as were the linear measures of scapular elevation and abduction. Thoracic kyphosis, protraction of the head and shoulders, and the diameter of the upper thoracic cage were also measured. ANOVA and the Student's t-test for dependent samples were used for the inter-group and intra-group comparisons, respectively. Findings: The COPD group exhibited significantly higher right (F[1.37]=6.12, p=0.0182;12.99 mm 95% CI, 12.43 to 13.52) and left (F[1.37]=10.21, p=0.0029; 12.35 mm, 95% CI, 11.81 to 12.89) scapula in comparison with the control group. The COPD group exhibited asymmetry in the scapular and cervical spine measurements than the control group (P<0.05). Interpretations: The greater scapular elevation in the group with COPD is likely due to the shortening of the upper trapezius muscle. The presence of postural asymmetry in individuals with COPD may favor the occurrence of pain in the scapular and cervical regions. Stretching exercises involving the upper trapezius muscle should be included in rehabilitation programs for individuals with COPD.